2013
DOI: 10.1021/ja409013m
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Spirocyclic Oxindole Alkaloids: Application of the Asymmetric Palladium-Catalyzed [3 + 2] Trimethylenemethane Cycloaddition

Abstract: The marcfortines are complex secondary metabolites that show potent anthelmintic activity and are characterized by the presence of a bicyclo[2.2.2]diazaoctane fused to a spirooxindole. Herein, we report the synthesis of two members of this family. The synthesis of marcfortine B utilizes a carboxylative TMM cycloaddition to establish the spirocyclic core, followed by an intramolecular Michael addition and oxidative radical cyclization to access the strained bicyclic ring system. In addition, the first asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(35 citation statements)
references
References 62 publications
0
34
0
1
Order By: Relevance
“…Oxindoles 378 and 381 were transformed to rac-374 and (À)-375, respectively, through an intramolecular Michael addition and an oxidative radical cyclization involving the formation of a bicyclo[2.2.2]diazaoctane moiety (Scheme 76). 137 Total syntheses of four spirocyclic oxindole alkaloids, corynoxine (383), corynoxine B (384), corynoxeine (385), and rynchophylline (386), were accomplished, which featured the assembly of tetracyclic spirooxindole intermediate 388 by the Tsuji-Trost allylic alkylation of a-keto ester 387 (Scheme 77). 138 Formal syntheses of ent-rynchophylline (ent-386) and entisorynchophylline (389) were reported.…”
Section: Tryptaminesmentioning
confidence: 99%
“…Oxindoles 378 and 381 were transformed to rac-374 and (À)-375, respectively, through an intramolecular Michael addition and an oxidative radical cyclization involving the formation of a bicyclo[2.2.2]diazaoctane moiety (Scheme 76). 137 Total syntheses of four spirocyclic oxindole alkaloids, corynoxine (383), corynoxine B (384), corynoxeine (385), and rynchophylline (386), were accomplished, which featured the assembly of tetracyclic spirooxindole intermediate 388 by the Tsuji-Trost allylic alkylation of a-keto ester 387 (Scheme 77). 138 Formal syntheses of ent-rynchophylline (ent-386) and entisorynchophylline (389) were reported.…”
Section: Tryptaminesmentioning
confidence: 99%
“…For example, S N 2' cyclizations of diketopiperazine (DKP) enolates were used by Williams' group in their approaches to both brevianamide B (I) [16,17] and stephacidin A (IV) [18][19][20][21][22], whereas Sarpong et al used an intramolecular enolate amidation [23]. Myers' [24] and Trost's [25,26] groups used radical cyclizations to construct the diazabicyclo[2.2.2]octane skeleton, whereas Simpkins' group developed both cationic [27][28][29] and radical [30,31] cyclization cascades to malbrancheamide B (V) and stephacidin A (IV), respectively. Baran and coworkers applied in contrast an intramolecular oxidative coupling of dienolates in their approach to IV [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of (±)-marcfortine B 358 began with the preparation of isopropylidene oxindole 339 from the known oxindole 338 in two steps (Scheme 64), and it subsequently underwent a highly efficient cycloaddition with silyl donor 340 in the presence of 5 mol% palladium(II) acetate and 35 mol% triisopropyl phosphite. 72,73 After hydrolytic workup and alkylation, methyl ester 341 was isolated in excellent yield as a 1:1 mixture of diastereomers. The use of dimethyl sulfate/potassium carbonate was chosen over the alternative conditions for methylation (eg, DCC/methanol or DBU/CH 3 I), and this minimized any isomerization of the double bond.…”
Section: Synthesis Of (-)-N-methylwelwitindolinone C Isothio Cyanatementioning
confidence: 99%
“…Trost et al also reported the synthesis of (-)-marcfortine C 375, 72 which started from commercially available 6-benzyloxyindole 359 using a known procedure 77 that involved Boc protection, benzyl ether hydrogenolysis, and copper-catalyzed propargylation to generate indole 361 in excellent overall yield (Scheme 68). The thermal Claisen rearrangement of 361 was known to proceed with the loss of the Boc group.…”
Section: Synthesis Of (-)-Marcfortine Cmentioning
confidence: 99%